مفهوم الأخلاق عند حامكا في كتابه "فلسفة الحياة" (FALSAFAH HIDUP) دراسة تقويمية - Adanan As'ari (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The present study was conducted with aim at evaluating (taqwim) the way Haji Abdul Malik Karim Amrulla (Hamka) defined, perceived and combined between theoretical (nazariyy) and practical (tasawwuf 'amaliyy) aspect of the philosophy of morality, an effort that, as far as the researcher is concerned, has no significant legal precedence. To obtain this objective, the researcher employed two methods, i.e. inductive (istiqra'i) and analytical (tahlili) approaches. The former was used to conclude Hamka's theory of morality; and the latter was employed to critically analyse such a theory. The study revealed that, firstly, despite his disagreement with a number of scholars, Hamka placed intellect a rank above the soul where this means that the former is the thing that generally leads human morality. However, the Minang-born scholar managed, secondly, to harmoniously synthesise between intellect and soul in such a way that the leader of behaviour, throughout his book, seems to be soul whereas it is in reality the intellect. Next to this, thirdly, Hamka also managed to translate the general outlook of morality (akhlaq) into the Indonesian context where it faced the Dutch and Japanese colonial regimes. He proved that what really awoke the Indonesian people at the time of the Dutch occupation was their intellect rather than soul so that they eventually obtained their independence. In doing so, Hamka's clarification on the centrality of the intellect rather than the soul in the big picture of moral theory has, little or much, influenced the pattern of the Indonesian educational philosophy system.